Biotechnology and Forestry - Kapoor, M. L. (Indian Forester, 1985)
Biotechnology is a sophisticated and advanced technology encompassing many disciplines of biosciences. It has evolved multidimensional approaches to solve certain problems at a much faster rate than known to the mankind in the recent past. Biotechnology promises to unfold many events of amazement in the near future, but its use should be with a caution of ethical scense. Tissue culture is one of the biotechniques which has agreat potential for improvement and mass clonal multiplication of forest trees. Micropropagation and embryogenesis can play a significant role in producing identical trees on a mass scale through clonal propagation. Somatic hybridization and haploid production are another areas of interest in forestry. The scope and application of biotechnology in forestry has been highlighted in this paper.